Appearances of Local Prolific Ewes in Semarang Regency Central Java Indonesia - Setiatin, Enny Tantini; Sutiyono, Sutiyono; Samsudewa, Daud; Sutopo, Sutopo; Ondho, Yon Soepri (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2021)
The present study examined the quantitative and qualitative physical parameters of prolific local ewes in Bawen and Jambu districts, Central Java. We used purposive sampling to select and categorized 132 local, three-lambing ewes into three groups based on their prolific capacity: 66 single, 49 twins and 17 triplets. The data were subjected to analysis of variance using Chi-Square. The result showed that many quantitative properties of prolific ewes resembled those of fat-tailed sheep: thin tail, highly significant (P<0.01) compared to fat tails; straight face, highly significant (P<0.01); and fewer convex face and short body, significant (P<0.05) with a tall body in the non-prolific ewes. Few prolific ewes had big ears and black-white wool and significantly different (P<0.05) from the non-prolific ewes. Conclusively, local prolific ewes had a qualitative appearance more closely related to that of thin-tailed ewes, but greater quantitative performances than the non-prolific ewes.